Exploring public relations and management communication - Tench, Ralph; Waddington, Stephen
"Exploring Public Relations began in Leeds in the early 2000s with a collaboration between myself and Dr Liz Yeomans. Through four editions of the book, and working with exceptional friends and fellow academic colleagues, this book has innovated and led the way in the field of public relations and strategic communication textbooks. A path that - as a clear complement to the project - many other writers around the world have emulated and copied. We still think Exploring Public Relations is the leading book to guide students, lecturers and observers of the practice, and we get regular feedback to reinforce this point. Since the 4th edition my good friend Liz has retired from full-time academic life. I must therefore convey my thanks to Liz for her friendship and collegial collaboration over the many years that we worked together and particularly on the four enjoyable versions of this book. Thank you, Liz"--Provided by publisher.